Factors associated with diabetic ketoacidosis at onset of Type 1 diabetes in children and adolescents. Issue 11 (9th July 2013) - de, L.; Oren, L.; Lazar, L.; Lebenthal, Y.; Shalitin, S.; Phillip, M.
Abstract Aims To identify risk factors for diabetic ketoacidosis at diagnosis of Type 1 diabetes in children and adolescents. Methods In three time periods (1986–1987, 1996–1997 and 2006–2007) 75, 86 and 245 patients, respectively, aged < 20 years were newly diagnosed with Type 1 diabetes in one tertiary care centre. In this retrospective comparative study, data of clinical characteristics, laboratory evaluation at diagnosis, as well as demographic data were retrieved from the patients' files. Comparative analyses were performed between patients presenting with or without diabetic ketoacidosis and between the three time periods. Results Patients presenting with diabetic ketoacidosis were younger (9.2 ± 4.7 vs. 10.4 ± 4.7 years; P < 0.02), thinner (weight standard deviation score –0.59 ± 1.2 vs. –0.25 ± 1.1; P = 0.002) and less frequently had a first‐ and/or second‐degree relative with Type 1 diabetes compared with those without diabetic ketoacidosis at presentation (16.0 vs. 31.2%, respectively; P = 0.001). Children with diabetic ketoacidosis were less likely to have had relevant testing before diagnosis than children without diabetic ketoacidosis. Children aged < 2 years presented more often with diabetic ketoacidosis than the older children (85 vs. 32%; P < 0.001). Children of Ethiopian origin had a higher rate of diabetic ketoacidosis at diagnosis than the rest of the cohort (57.8 vs. 33%; P = 0.04). Conclusions Factors affecting the risk of developing diabetic ketoacidosis at diagnosis of Type 1 diabetes may be related to the degree of awareness of symptoms of diabetes among parents and primary care physicians. Prevention programmes should aim at increasing awareness and consider the application of special measures to avoid diabetic ketoacidosis in children aged < 2 years and high‐risk ethnic groups.